Diversity of avifauna in the orchards of the Republic of Moldova - Tudor Țibuleac; Teodor Glăvan-Caranghel; Victoria Nistreanu (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The study was conducted in the period 1991-2018 in 86 different types of orchards from the central part of the Republic of Moldova, in all phenological periods. The bird fauna in the orchards is well represented, with a rich diversity of 95 species from 13 orders, which represents 35% of the avifauna of the republic. The dominant species were the passerine birds that are widespread and have high density in various arboreal biotopes. There were recorded 5 protected species: Ciconia ciconia, Circus pygargus, Milvus migrans, Falco vespertinus and Dendrocopos medius. In terms of phenology, the predominance of migratory species was found, followed by sedentary ones, winter guests, occasional and passage species. Further research is needed on orchard avifauna, which provide a range of economically valuable ecosystem services.